VOLUNTEERING AS A FACTOR IN THE FORMATION OF MORAL STANDARDS AMONG YOUNG PEOPLE - N. V. Popova; E. V. Popova (Russian State Vocational Pedagogical University, 2018)
Introduction. Volunteering is a socially significant activity, which contributes to solving separate acute social issues and showing the best qualities of an individual - compassion, ability to sympathise and readiness to provide assistance to people in need. Through volunteering, a person achieves self-esteem and a feeling of his or her relevance and usefulness. Under the present circumstances, aspects of the study of volunteering and youth attitudes to this concept are especially relevant. Over the last decades, social transformations have occurred, leading to a reassessment of the value system, and, consequently, society has lost its moral compass. Participation in volunteering can become one of the effective factors in the formation of ethical standards and humanistic value orientations among young people.The aim of the research was to investigate the educational potential of volunteering through studying the attitudes of young people.Methodology and research methods. The research was based on axiological and sociological approaches. In the course of the research, the following methods were used: review and synthesis of historical-philosophical and sociological literature, sociological group face-to-face surveys, and comparative analysis of statistical data. Results and scientific novelty. The authors justified the necessity for moral education of working youth through the involvement of young people in realizing charitable projects and organising philanthropic events. The authors highlighted the aspects of conducting charitable activities in one of the socially-oriented enterprises of the Urals - Sinarsky Pipe Plant. A questionnaire based survey conducted among young workers of that metal manufacturer revealed the fact of mass participation in various charitable activities (out of the sample seize of 180 young workers, 89% of respondents admitted their involvement in philanthropic activities). The respondents expressed interest in charitable projects and readiness to spend own time, energy and money for rendering disinterested targeted assistance to children with special needs and children with disabilities (56.3%), to elderly people living in difficult life situations (52.5%), to stray animals (50.0%), to children suffering from cancer (49.3%). It was concluded that charity work forms ethical standards at young people, and develops altruistic qualities such as disinterestedness and responsiveness, as well as civil consciousness.Practical significance. The research outcomes can be used when preparing, organising and holding charitable work with the aim of bringing up morally and ethically educated young workers, as well as students of educational institutions of different levels.